2015
DOI: 10.1007/s10549-015-3587-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular subtyping improves diagnostic stratification of patients with primary breast cancer into prognostically defined risk groups

Abstract: Combined use of MammaPrint and a molecular subtyping profile (BluePrint) identifies disease subgroups with marked differences in long-term outcome and response to neo-adjuvant therapy. The aim of this study was to evaluate the prognostic value of molecular subtyping using MammaPrint and BluePrint in women with early-stage breast cancer (BC) treated at US institutions following National Comprehensive Cancer Network standard guidelines. Tumor samples were collected from stage 1-2B consecutively diagnosed BC pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 16 publications
1
23
0
Order By: Relevance
“…Notably, 22% of over 400 breast cancer patients studied were reclassified into a different subgroup compared with conventional assessment and showed an improved distribution of response rates in the relevant treatment groups. Similar findings were reported by Yao et al 12 Previous studies have shown that mRNA reporting of ER, PR and HER2 using microarrays is highly comparable to IHC testing. [13][14][15] However, others have cautioned against the preferential use of hormone receptor reports using RNA-based reverse transcription polymerase chain reaction (RT-PCR) technology, highlighting discordance with the IHC results and the potential of denying patients who were ER or PR positive on IHC the benefit of endocrine therapy.…”
Section: Introductionsupporting
confidence: 90%
“…Notably, 22% of over 400 breast cancer patients studied were reclassified into a different subgroup compared with conventional assessment and showed an improved distribution of response rates in the relevant treatment groups. Similar findings were reported by Yao et al 12 Previous studies have shown that mRNA reporting of ER, PR and HER2 using microarrays is highly comparable to IHC testing. [13][14][15] However, others have cautioned against the preferential use of hormone receptor reports using RNA-based reverse transcription polymerase chain reaction (RT-PCR) technology, highlighting discordance with the IHC results and the potential of denying patients who were ER or PR positive on IHC the benefit of endocrine therapy.…”
Section: Introductionsupporting
confidence: 90%
“…Based on the expression of 80-genes, a molecular subtyping profile (“BluePrint”) has been developed for the stratification of breast cancer tumors into the three main molecular subtypes: luminal, HER2 and basal [ 13 ]. By adding the prognostic risk profile of the 70-gene signature (70-GS), a substratification of luminal-type tumors into low risk (luminal A) and high risk (luminal B) type cancers can be made [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ten-year follow-up data in patients receiving systemic adjuvant therapy [ 28 ] and 5-year outcome data in the neoadjuvant setting [ 7 ] have shown that BluePrint classification is more strongly associated with CT response than IHC/FISH subtyping. In the MINDACT study, 16% of the patients were re-stratified to the low-risk luminal A group by BluePrint and had 95% 5y-DMFS [ 15 , 29 ].…”
Section: Discussionmentioning
confidence: 99%